The Practice of International Phonectic Alphabet among Students of the English Department of Sriwijaya Polytechnic: - - -, Moehamad Ridhwan; Herman (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2022)
Abstract: This study was conducted for the purpose of investigating the students’ use of International Phonetic Alphabet in the English Department of State Polytechnic of Sriwijaya. It is well known that English words are difficult to read and pronounce due to several factors. For instance, most of the words are not pronounced the way they are spelled. In other words, the letters in English alphabet are not always the exact representation of the sounds they are trying to symbolize in the written form. Therefore, the writers were in great intention of pointing out that there was a solution that would put an end to it called the International Phonetic alphabet. Besides, the writers were also curious about the students’ familiarity towards the English phonetic symbols. After the study was completed, it was found that the majority of the students were still unaware of the existence the International Phonetic Alphabet and thus, they were not in the practice of using it properly to improve their English pronunciation. Keywords: International Phonetic Alphabet, pronounce, sound, symbol